GIP1 and GIP2 Contribute to the Maintenance of Genome Stability at the Nuclear Periphery - Singh, Gaurav; Batzenschlager, Morgane; Tomkova, Denisa; Herzog, Etienne; Hoffmann, Elise; Houlné, Guy; Schmit, Anne-Catherine; Berr, Alexandre; Chabouté, Marie-Edith (Frontiers in Plant Science, 2022)
The maintenance of genetic information is important in eukaryotes notably through mechanisms occurring at the nuclear periphery where inner nuclear membrane proteins and nuclear pore-associated components are key factors regulating DNA damage responses (DDR). However, this aspect of the regulation of DDR is still poorly documented in plants. We addressed here how genomic stability is impaired in the gamma-tubulin complex component 3-interacting protein (gip1gip2) double mutants showing defective nuclear shaping. Using neutral comet assays for DNA double-strand breaks (DSBs) detection, we showed that GIP1 or GIP2 act redundantly to maintain genome stability. At the cellular level, -H2AX foci in gip1gip2 were more abundant and heterogeneous in their size compared to WT in root meristematic nuclei, indicative of a constitutive DNA damage. This was linked to a constitutive activation of the DDR in the gip1gip2 mutant, with more emphasis on the homologous recombination (HR) repair pathway. In addition, we also noticed the presence of numerous RAD51 foci which did not colocalize with -H2AX foci. The expression of GIP1-GFP in the double mutant rescued the cellular response to DNA damage, leading to the systematic colocalization of RAD51 and -H2AX foci. Interestingly, a significant proportion of RAD51 foci colocalized with GIP1-GFP at the nuclear periphery. Altogether, our data suggest that GIPs may partly contribute to the spatio-temporal recruitment of RAD51 at the nuclear periphery.